2012
DOI: 10.1007/s13632-012-0024-x
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Oxidation of Pt–Al–Cr–Ru Alloy: Scale Morphology and Adherence

Abstract: Heat-treated Pt-11Al-3Cr-2Ru (at.%) alloy samples were oxidized in air for periods between 1 and 500 h in a muffle furnace at 1350°C. The morphology of the oxidized samples was examined using light microscopy and scanning electron microscopy equipped with energy dispersive spectroscopy, while an x-ray diffractometer and Raman spectroscopy were used for phase identification. The scale layers were found to be composed mainly of a-Al 2 O 3 ; they were adherent, continuous, and protective with neither a zone of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…3 and 4). This is similar to observation on current alloy oxidized at 1150, 1250°C, 28 and 1350°C. [29][30][31] Surface morphologies of the scale layers revealed that the scales grew from submicron thin films to coarse, large, irregular-shaped grains.…”
Section: Oxide Scale Characterizationsupporting
confidence: 91%
See 1 more Smart Citation
“…3 and 4). This is similar to observation on current alloy oxidized at 1150, 1250°C, 28 and 1350°C. [29][30][31] Surface morphologies of the scale layers revealed that the scales grew from submicron thin films to coarse, large, irregular-shaped grains.…”
Section: Oxide Scale Characterizationsupporting
confidence: 91%
“…As the scale thickness increases with increasing oxidation time, the stress induced in the substrate also increased. In addition, the tendency for the substrate to relieve the stresses by creep also increased at higher temperatures .…”
Section: Resultsmentioning
confidence: 99%
“…The Platinum group metals (PGMs), such as Pt, Ru, Os, Rh, Pd, and Ir, for high-temperature structural applications has been investigated [9][10][11][12]. Despite their chemical properties resembling those of Nickel-based super-alloys (NBSAs) [13], some PGMs are inherently brittle and face challenges related to weight and cost.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recent studies have explored intermetallic alloys of magnesium with elements like lanthanum, neodymium, and samarium across various crystallographic phases such as D0c, A15, and L1 2 , employing ab initio density functional theory calculations. 6,7 Notably, data on the heat of formation suggest thermodynamic stability across all these phases. Furthermore, these alloys exhibit mechanical stability, albeit with exceptions in the L1 2 and A15 phases.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of platinum group metals (PGMs) like platinum, ruthenium, osmium, rhodium, palladium, and iridium has also been explored for high-temperature structural applications. [6][7][8][9] Although their chemical characteristics are akin to those of nickel-based super-alloys (NBSAs), 10 certain PGMs possess inherent brittleness and encounter obstacles associated with weight and cost. Previously, Raub et al 11 and Greenfield et al 12 confirmed the presence of three intermetallic compounds-Cr 4 Ru, Cr 3 Ru, and Cr 2 Ru (s phase)-in the Cr-Ru binary phase diagram, 13 as well as the terminal solution phases of BCC (Cr) and HCP (Ru), using metallography, X-ray diffraction (XRD), and microhardness assessment techniques.…”
Section: Introductionmentioning
confidence: 99%